Fatores explicativos do nível de evidenciação nas páginas eletrônicas de municípios do sul do Brasil - Machado, Vagner Naysinger (Universidade do Vale do Rio dos Sinos, 2014)
The aim of this thesis was to identify the factors that explain the level of disclosure (NE) of the most populous municipalities of southern Brazil, on the respective web pages published on the internet . In this sense, the Legitimacy Theory assumes that the process of legitimation of public management would be linked to the fulfillment of the social contract. What would be threatened by the occurrence of the information asymmetry matter. One way to minimize this problem and reaffirm the legitimacy of public managers would be the adoption of good governance, especially transparency through the disclosure of public information. In this theoretical background, there is the review of national and international empirical studies regarding transparency and disclosure of public management. Furthermore, we investigated the Brazilian legislation focusing on the disclosure and access to information concerning the public sector. Thus, we constructed a set of 86 indicators of information. The analysis of web pages towards the disclosure of these indicators made it possible to measure the level of disclosure of public management. In this sense, to identify factors that explain the level of disclosure, a set of hypotheses was formulated, with the assumption that there is a relation between these factors and the NE from these municipalities. In order to test these hypotheses, we built a set of variables, which were submitted to the statistical technique of multiple linear regression. The results of the estimated statistical model indicate that the factors that influence the legitimation process of public management and explain the level of disclosure of the municipalities is the IFDM, the current net revenue and the mayor’s political party. Furthermore, the factors that explain the level of disclosure of mandatory information is the GDP per capita and the IFDM from the municipalities. And the factors that explain the level of disclosure of voluntary information is the GDP per capita, the population and the IFDM. By investigating what would lead public managers to disclose information about their government, this dissertation will be able to guide the development of effective policies of transparency and disclosure of public information.
Keywords: Evidenciação; Fatores explicativos; Gestão pública municipal; Disclosure; Explanatory factors; Public municipal management; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis